THE PECULIARITIES OF A SOCIAL MYTHOLOGY SYSTEM GENERATION OF TURKMENISTAN - Аулін, О. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the specific of forming of the system of social mythology of Turkmenistan in the context of possible consequences for Ukrainian socium is examined.